Β-modification of isotactic polypropylene induced by electrospun isotactic polystyrene fibers. (2nd August 2019) - Wang, Chi; Lee, Jheng Lin; Landingin, Junard; Ko, Chia-Hsin
Abstract: Isotactic polypropylene (iPP) composites filled with electrospun isotactic polystyrene (iPS) fibers were prepared through solution blending by sonication in a nonsolvent water bath. After optimal sonication treatments, the entangled and surface-fused iPS fibers in the nonwoven fabrics were disentangled and separated to facilitate better dispersion in the as-prepared composites. Composites with different fiber concentrations (0.01, 0.1, and 1 wt%) subjected to various thermal treatments were characterized using DSC, POM, and simultaneous WAXD/SAXS. The effects of cooling rates and crystallization temperatures on the formation of β -form crystals and lamellar morphology were extensively studied. Results showed that electrospun iPS fibers are novel β -nucleating agent towards iPP to enhance crystallization rate. A β -form content of ∼50% was achieved at a fiber concentration of 0.1 wt%, and the β -form content increased with increasing cooling rate. Under isothermal crystallization, the maximum β -form content was found at 120 °C, lying between the T αβ and T βα ; the former is associated with α -to- β and the latter is relevant to the β -to- α crystal transformation due to the difference in the growth rates of both α and β phases. This finding is consistent with POM observations, revealing that a transcrystalline layer of dense α -form nuclei is first induced at the iPS fiber surface for initial crystal growth, followed by α -to- β bifurcation growth to develop highly birefringent β -form crystals. The average lamellar thickness derived from SAXS results is dependent on the supercooling degree, as well as on the relative content of α/β crystals developed in the composites. Graphical abstract: Image 1 Highlights: Electrospun iPS fibers are found to be dual-nucleating agent for iPP to produce both the α and β phases. A β -form content of ∼50% is achieved at a fiber concentration of 0.1 wt%.